IBM KELOMPOK USAHA PENGRAJIN BATIK - Basuki Widodo; Susi Budi Astuti; Tri Rahayuningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
If during the two partners just sell fabrics, it should be developed to sell in some form of hand made products. It is made from batik, all of which can be categorized as a souvenir. Batik in the form of souvenirs still has its own market share, that is the purpose of domestic tourists, foreign tourists as well as for celebrations such as weddings. The next obstacle is related to the production of a narrow space. Ideally batik production has space sized sufficiently broad and flexible to produce it. But in both partners, it is very narrow production space. Production stages are still allows for optimized drying stages using a drying design of effective and efficient, so it can be argued that the drying apparatus in accordance with the terms intensive. However, the increasing production to be followed without by having the expansion of space / area. In addition, to design those things need to be considered in making the selection of material drying apparatus. Because when using the metal material will result corrosion process. The next obstacle was until recently run marketing is conventional marketing that relied on information 'word of mouth' is through the information passed from neighbor to relatives or friends, or just by using the card. Consumers are loyal employees, teachers and the general public who want batik for uniforms purposes. The resulting agreement between the partners and the proposer of activities in an attempt to overcome the problems that arise in the partner. The activities are doing the training and mentoring the design and manufacture of souvenirs made from batik, as well as the drying equipmemt needed to support the improvement of the production process. And also training on consolidation marketing theory and application of on-line marketing.Keywords: souvenir, online marketing, diversification and intensification